(3GdUGaj aj cdGe Gddgs - (3eMeO eMSf Hf eQJVi Hf eMehO , GdTgjQ HGdajV GdcGTGfj , J (B1091 (3g`s ((3eNa Ydi Hf fHGR Ydi GdWGdYGfi GdYQai s)
(3ChdgG (B:s
(3SHMGf GdPi CSQi HYHOg djdkG ef GdeSLO GdMQGe Edi GdeSLO GdCbUi GdPi HGQcfG Mhdg s
(3BNQgG (B:s
(3ef GdMhQ GdYjf hRGO ai GdeLeY hCScfg Gddg ai LfI YOf hSW GdLfI eY GdfHjjf hGdeQSdjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJaSjQ hYdhe GdbQBfs